Evaluation of safety, immunogenicity, and efficacy of inactivated reverse-genetics-based H5N8 highly pathogenic avian influenza virus vaccine with various adjuvants via parenteral and mucosal routes in chickens - Tabynov, Kairat; Kuanyshbek, Aidana; Yelchibayeva, Leila; Zharmambet, Kuantay; Zhumadilova, Zauresh; Fomin, Gleb; Petrovsky, Nikolai; Shekoni, Olaitan C.; Renukaradhya, Gourapura J.; Tabynov, Kaissar (Frontiers in Immunology, 2025)
BackgroundHighly pathogenic H5Nx avian influenza (HPAI) poses a significant threat to poultry health globally, necessitating the development of effective vaccination strategies.MethodsThis study assessed the immunogenicity and efficacy of a reverse-genetics-derived, Differentiating Infected from Vaccinated Animals (DIVA)-compatible inactivated H5N8 vaccine based on the IDCDC-RG71A strain. The vaccine was formulated with different adjuvants, including Montanide ISA 78 VG, ISA 71 R VG, GEL P PR, and mannose-conjugated chitosan nanoparticles, and administered via either the subcutaneous (SC) or intranasal (IN) route. To evaluate safety, the vaccine was tested in specific antibody negative (SAN) chickens, showing no adverse effects. Immunogenicity was assessed by measuring hemagglutination inhibition (HI) antibody titers, antigen-specific IgA and IgY levels, and CD4+ and CD8+ T cell proliferation. Vaccine efficacy was determined through a challenge study using a field isolate of H5N1.ResultsThis showed that a single SC dose of vaccine containing ISA 78 VG or ISA 71 R VG provided the best efficacy against infection, with high survival rates, control of abnormally high temperature incidence, reduced virus shedding, and reduced lung and liver lesions. The ISA 78 VG-adjuvanted SC vaccine induced the highest HI titers and CD4+ T cell proliferation, while ISA 71 R VG and GEL P PR elicited the strongest IgY responses. In contrast, IN formulations induced IgA in the lungs and trachea however, even after two doses, failed to generate high HI titers and provided poor, if any, protection against infection. This highlights the superior efficacy of the SC over the IN route of vaccination for reducing H5N1 viral shedding.ConclusionThese results underscore the importance of both the adjuvants and delivery route to maximize HPAI vaccine efficacy. This presented system could thereby be used to develop potent and DIVA-compatible vaccines to enhance biosecurity and disease management in regions affected by endemic HPAI.